A two-component waterborne polyurethane adhesive and its preparation method and application
By optimizing the formulation of epoxy primer and polyurethane topcoat and introducing surface hydrophobic agents, the problem of insufficient water resistance of two-component water-based polyurethane adhesives is solved, and stronger water resistance and hydrophobic properties are achieved, which is suitable for building waterproofing applications.
Patent Information
- Application Number
- CN202410944920.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-15
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-07-15
AI Technical Summary
The swelling and peeling problems of two-component water-based polyurethane adhesive in water lead to insufficient water resistance.
By optimizing the formulation of epoxy primer and polyurethane topcoat, combined with the introduction of surface hydrophobic agents, the intermolecular action force and molecular chain alignment density are improved, and water resistance and hydrophobic properties are enhanced.
It significantly improves the water resistance and hydrophobic properties of two-component water-based polyurethane adhesives, and is suitable for building waterproofing applications.
Smart Images

Figure BDA0004945348740000121 
Figure BDA0004945348740000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyurethane adhesives, and specifically relates to a two-component water-based polyurethane adhesive and a preparation method and application thereof. Background Art
[0002] Due to its good elasticity, wear resistance and corrosion resistance, polyurethane is widely used in the construction field. At present, polyurethane adhesives can be divided into one-component polyurethane adhesives and two-component polyurethane adhesives according to their composition. Although two-component polyurethane adhesives have excellent mechanical properties and strong corrosion resistance, there are a large number of hydrophilic groups in the polyurethane molecular chain. These hydrophilic groups will form hydrogen bonds with water molecules when they meet water, causing the polyurethane adhesive to swell and peel off in water. Therefore, improving the water resistance of two-component water-based polyurethane adhesives has become the focus of current research. Summary of the invention
[0003] The object of the present invention is to provide a two-component waterborne polyurethane adhesive and a preparation method and application thereof, so as to improve the water resistance of the two-component waterborne polyurethane adhesive.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing a two-component waterborne polyurethane adhesive comprises the following steps: uniformly mixing an epoxy primer and a polyurethane topcoat in a volume ratio of 1-1.2:1.5-2.5 to obtain the two-component waterborne polyurethane adhesive;
[0006] The preparation method of the epoxy primer comprises the following steps:
[0007] S11, polyethylene glycol monomethyl ether 2000 (purchased from Sichuan Puxi'ao Standard Material Technology Co., Ltd.), dodecyl succinic anhydride, phthalic anhydride were mixed, heated and stirred at 90-100° C. for 3-4 hours, epoxy resin E51 (purchased from Jinan Jumeihui Chemical Co., Ltd.) and triphenylphosphine were added, heated and stirred at 110-120° C. for 3-4 hours to obtain material A;
[0008] S12, take the material A, deionized water and mix, stir for 5-7h, add dipropylene glycol butyl ether, propylene glycol methyl ether, defoamer GP-330 (purchased from Nantong Chenrun Chemical Co., Ltd.), Digo BYK153 wetting agent (purchased from Dongguan Gaosijin Lightweight Building Materials Manufacturing Co., Ltd.), BASF dispersant Tamol NN 9401 (purchased from Guangdong Yunxing Biotechnology Co., Ltd.), mixed etherified glycoluril resin (purchased from Hubei Jiangmin Taihua Chemical Co., Ltd.), sodium nitrite, calcium ion exchange silica antirust pigment (purchased from Shanghai Yisheng Chemical Co., Ltd.), Bick BYK410 rheological additive (purchased from Shanghai Buding Chemical Co., Ltd.), stir for 4-5h, and obtain the epoxy primer;
[0009] The preparation method of the polyurethane topcoat comprises the following steps:
[0010] S21, mixing butyl-decanoic acid, terephthalic acid methanol and diphenyl phosphate, and stirring for 10-12 hours to obtain material B;
[0011] S22, mixing graphene oxide powder, deionized water, p-phenylenediamine and ammonia water, dispersing by ultrasonic at 80-90° C. for 2-3 h, filtering, washing and drying the solid phase to obtain material C;
[0012] S23, taking the material C, deionized water, and dodecylbenzenesulfonic acid, mixing them, ultrasonically dispersing them at 40-50° C. for 2-3 hours, adding aniline, stirring for 10-20 minutes, adding ammonium persulfate, stirring in an ice-water bath for 6-8 hours, filtering, washing the solid phase, and drying to obtain material D;
[0013] S24, taking the material D, hydrophobic fumed silica, anhydrous ethanol, and polydimethylsiloxane, mixing them, ultrasonically dispersing them for 1-2 hours, drying them at 50° C. for 4-6 hours, filtering them, washing the solid phase, and drying them to obtain the surface hydrophobic agent;
[0014] S25. In a condensing reflux reactor, take isophorone diisocyanate, 4-methoxyphenol, dibutyltin dilaurate, and ethyl acetate, mix, stir for 20-30 min, add triethylene glycol, stir at 35-45 ° C for 20-30 min, heat to 50 ° C, continue stirring for 2-3 h, heat to 55-65 ° C, add material B, stir for 2-3 h, heat to 80 ° C, add hydroxyethyl acrylate, stir for 3-4 h, filter, take the liquid phase, add acrylate isobornyl ester, adhesion promoter JSC-505 (purchased from Hangzhou Jessica Chemical Co., Ltd.), and surface hydrophobic agent, stir for 2-3 h, and obtain the polyurethane topcoat.
[0015] As a preferred technical solution of the present invention, in step S11, the mass ratio of polyethylene glycol monomethyl ether 2000, dodecyl succinic anhydride, phthalic anhydride, epoxy resin E51, and triphenylphosphine is 25-30:2-3:0.8-1:80-90:0.1-0.2.
[0016] As a preferred technical solution of the present invention, in step S12, the mass ratio of material A, deionized water, dipropylene glycol butyl ether, propylene glycol methyl ether, defoamer GP-330, Digo BYK153 wetting agent, BASF dispersant Tamol NN 9401, mixed etherified glycoluril resin, sodium nitrite, calcium ion exchange silica anti-rust pigment, and BYK410 rheological additive is 40-50:20-30:0.2-0.4:0.1-0.2:0.2-0.4:0.1-0.2:0.1-0.2:0.5-0.6:0.1-0.2:0.05-0.06:0.1-0.2.
[0017] As a preferred technical solution of the present invention, in step S21, the mass ratio of butyl-decanoic acid ketone, 4-dimethylol and diphenyl phosphate is 6-7: 1-1.2: 0.2-0.3.
[0018] As a preferred technical solution of the present invention, in step S22, the dosage ratio of the graphene oxide powder, deionized water, p-phenylenediamine, and ammonia water is 50 mg: 100 mL: 0.3-0.4 g: 0.6-0.8 mL; the concentration of the ammonia water is 1-2 mol / L.
[0019] As a preferred technical solution of the present invention, in step S23, the mass ratio of the material C, deionized water, dodecylbenzenesulfonic acid, aniline and ammonium persulfate is 0.2-0.4:50:0.02-0.04:1-1.2:0.02-0.04.
[0020] As a preferred technical solution of the present invention, in step S24, the mass ratio of the material D, hydrophobic fumed silica, anhydrous ethanol and polydimethylsiloxane is 1-2: 0.4-0.45: 70-80: 0.1-0.12.
[0021] As a preferred technical solution of the present invention, in step S25, the mass ratio of isophorone diisocyanate, 4-methoxyphenol, dibutyltin dilaurate, ethyl acetate, triethylene glycol, material B, hydroxyethyl acrylate, isobornyl acrylate, adhesion promoter JSC-505, and surface hydrophobic agent is 60-70: 1-1.2: 0.06-0.08: 20-25: 1-2: 1-2: 2-3: 0.6-0.8: 0.2-0.3: 0.8-1.2.
[0022] The two-component waterborne polyurethane adhesive is prepared by the above-mentioned preparation method.
[0023] As a preferred technical solution of the present invention, the application of the two-component water-based polyurethane adhesive refers to its use for building waterproofing.
[0024] Beneficial effects of the present invention:
[0025] The invention discloses a two-component waterborne polyurethane adhesive and a preparation method and application thereof. By optimizing the epoxy primer formula, the intermolecular force of the prepared two-component waterborne polyurethane adhesive is made stronger, the molecular chain arrangement is made more compact, and the water resistance thereof is improved. Meanwhile, a surface hydrophobic agent is introduced to improve the hydrophobic property of the waterborne polyurethane adhesive. DETAILED DESCRIPTION
[0026] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0027] Example 1
[0028] A method for preparing a two-component waterborne polyurethane adhesive, characterized in that it comprises the following steps: uniformly mixing an epoxy primer and a polyurethane topcoat in a volume ratio of 1:1.5 to obtain the two-component waterborne polyurethane adhesive;
[0029] The preparation method of the epoxy primer comprises the following steps:
[0030] S11, take polyethylene glycol monomethyl ether 2000, dodecyl succinic anhydride, phthalic anhydride, mix, heat and stir at 90 ° C for 3 hours, add epoxy resin E51 and triphenylphosphine, heat and stir at 110 ° C for 3 hours, and obtain material A; the mass ratio of polyethylene glycol monomethyl ether 2000, dodecyl succinic anhydride, phthalic anhydride, epoxy resin E51, and triphenylphosphine is 25:2:0.8:80:0.1;
[0031] S12, take the material A and deionized water, mix them, stir for 5 hours, add dipropylene glycol butyl ether, propylene glycol methyl ether, defoamer GP-330, Digo BYK153 wetting agent, BASF dispersant Tamol NN 9401, mixed etherified glycoluril resin, sodium nitrite, calcium ion exchange silica anti-rust pigment, BYK410 rheological additive, stir for 4 hours to obtain the epoxy primer; the material A, deionized water, dipropylene glycol butyl ether, propylene glycol methyl ether, defoamer GP-330, Digo BYK153 wetting agent, BASF dispersant Tamol NN 9401, the mass ratio of mixed etherified glycoluril resin, sodium nitrite, calcium ion exchange silica anti-rust pigment and BYK410 rheological additive is 40:20:0.2:0.1:0.2:0.1:0.1:0.5:0.1:0.05:0.1;
[0032] The preparation method of the polyurethane topcoat comprises the following steps:
[0033] S21, mixing butyl-decanoic acid ketone, terephthalic acid methanol and diphenyl phosphate, stirring for 10 hours to obtain material B; the mass ratio of butyl-decanoic acid ketone, terephthalic acid methanol and diphenyl phosphate is 6:1:0.2;
[0034] S22, mixing graphene oxide powder, deionized water, p-phenylenediamine and ammonia water, ultrasonically dispersing at 80° C. for 2 h, filtering, washing the solid phase, and drying to obtain material C; the amount ratio of the graphene oxide powder, deionized water, p-phenylenediamine and ammonia water is 50 mg: 100 mL: 0.3 g: 0.6 mL; the concentration of the ammonia water is 1 mol / L;
[0035] S23, taking the material C, deionized water, and dodecylbenzenesulfonic acid, mixing, ultrasonically dispersing at 40°C for 2h, adding aniline, stirring for 10min, adding ammonium persulfate, stirring in an ice-water bath for 6h, filtering, washing the solid phase, and drying to obtain material D; the mass ratio of the material C, deionized water, dodecylbenzenesulfonic acid, aniline, and ammonium persulfate is 0.2:50:0.02:1:0.02;
[0036] S24, taking the material D, hydrophobic fumed silica, anhydrous ethanol, and polydimethylsiloxane, mixing, ultrasonically dispersing for 1 hour, drying at 50° C. for 4 hours, filtering, washing the solid phase, and drying to obtain the surface hydrophobic agent; the mass ratio of the material D, hydrophobic fumed silica, anhydrous ethanol, and polydimethylsiloxane is 1:0.4:70:0.1;
[0037] S25. In a condensing reflux reactor, mix isophorone diisocyanate, 4-methoxyphenol, dibutyltin dilaurate and ethyl acetate, stir for 20 min, add triethylene glycol, stir at 35-45 ° C for 20 min, heat to 50 ° C, continue stirring for 2 h, heat to 55 ° C, add material B, stir for 2 h, heat to 80 ° C, add hydroxyethyl acrylate, stir for 3 h, filter, take the liquid phase, add acrylate isobornyl, Adhesion promoter JSC-505 and surface hydrophobic agent are stirred for 2 hours to obtain the polyurethane topcoat; the mass ratio of isophorone diisocyanate, 4-methoxyphenol, dibutyltin dilaurate, ethyl acetate, triethylene glycol, material B, hydroxyethyl acrylate, isobornyl acrylate, adhesion promoter JSC-505 and surface hydrophobic agent is 60:1:0.06:20:1:1:2:0.6:0.2:0.8.
[0038] Example 2
[0039] A method for preparing a two-component waterborne polyurethane adhesive, characterized in that it comprises the following steps: uniformly mixing an epoxy primer and a polyurethane topcoat in a volume ratio of 1.1:2 to obtain the two-component waterborne polyurethane adhesive;
[0040] The preparation method of the epoxy primer comprises the following steps:
[0041] S11, take polyethylene glycol monomethyl ether 2000, dodecyl succinic anhydride, phthalic anhydride and mix, heat and stir at 95 ° C for 3.5 hours, add epoxy resin E51 and triphenylphosphine, heat and stir at 115 ° C for 3.5 hours to obtain material A; the mass ratio of polyethylene glycol monomethyl ether 2000, dodecyl succinic anhydride, phthalic anhydride, epoxy resin E51 and triphenylphosphine is 28:2.5:0.9:85:0.15;
[0042] S12, take the material A and deionized water, mix them, stir for 6 hours, add dipropylene glycol butyl ether, propylene glycol methyl ether, defoamer GP-330, Digo BYK153 wetting agent, BASF dispersant Tamol NN 9401, mixed etherified glycoluril resin, sodium nitrite, calcium ion exchange silica anti-rust pigment, BYK410 rheological additive, stir for 4.5 hours to obtain the epoxy primer; the material A, deionized water, dipropylene glycol butyl ether, propylene glycol methyl ether, defoamer GP-330, Digo BYK153 wetting agent, BASF dispersant Tamol NN 9401, the mass ratio of mixed etherified glycoluril resin, sodium nitrite, calcium ion exchange silica anti-rust pigment and BYK410 rheological additive is 45:25:0.3:0.15:0.3:0.15:0.15:0.55:0.15:0.055:0.15;
[0043] The preparation method of the polyurethane topcoat comprises the following steps:
[0044] S21, taking butyl-decanoic acid ketone, terephthalic acid methanol, and diphenyl phosphate, mixing, stirring for 11 hours, and obtaining material B; the mass ratio of butyl-decanoic acid ketone, terephthalic acid methanol, and diphenyl phosphate is 6.5:1.1:0.25;
[0045] S22, mixing graphene oxide powder, deionized water, p-phenylenediamine and ammonia water, ultrasonically dispersing at 85° C. for 2.5 h, filtering, washing the solid phase, and drying to obtain material C; the amount ratio of the graphene oxide powder, deionized water, p-phenylenediamine and ammonia water is 50 mg: 100 mL: 0.35 g: 0.7 mL; the concentration of the ammonia water is 1.5 mol / L;
[0046] S23, take the material C, deionized water, and dodecylbenzenesulfonic acid, mix them, ultrasonically disperse them at 45°C for 2.5h, add aniline, stir for 15min, add ammonium persulfate, stir in an ice-water bath for 7h, filter, wash the solid phase, and dry to obtain material D; the mass ratio of the material C, deionized water, dodecylbenzenesulfonic acid, aniline, and ammonium persulfate is 0.3:50:0.03:1.1:0.03;
[0047] S24, taking the material D, hydrophobic fumed silica, anhydrous ethanol, and polydimethylsiloxane, mixing, ultrasonically dispersing for 1.5 hours, drying at 50° C. for 5 hours, filtering, washing the solid phase, and drying to obtain the surface hydrophobic agent; the mass ratio of the material D, hydrophobic fumed silica, anhydrous ethanol, and polydimethylsiloxane is 1.5:0.43:75:0.11;
[0048] S25. In a condensing reflux reactor, mix isophorone diisocyanate, 4-methoxyphenol, dibutyltin dilaurate, and ethyl acetate, stir for 25 minutes, add triethylene glycol, stir at 40°C for 25 minutes, heat to 50°C, continue stirring for 2.5 hours, heat to 60°C, add material B, stir for 2.5 hours, heat to 80°C, add hydroxyethyl acrylate, stir for 3.5 hours, filter, take the liquid phase, add acrylate isobornyl, adhesion Accelerator JSC-505 and surface hydrophobic agent are stirred for 2.5 hours to obtain the polyurethane topcoat; the mass ratio of isophorone diisocyanate, 4-methoxyphenol, dibutyltin dilaurate, ethyl acetate, triethylene glycol, material B, hydroxyethyl acrylate, isobornyl acrylate, adhesion promoter JSC-505 and surface hydrophobic agent is 65:1.1:0.07:23:1.5:1.5:2.5:0.7:0.25:1.
[0049] Example 3
[0050] A method for preparing a two-component waterborne polyurethane adhesive, characterized in that it comprises the following steps: uniformly mixing an epoxy primer and a polyurethane topcoat in a volume ratio of 1.2:2.5 to obtain the two-component waterborne polyurethane adhesive;
[0051] The preparation method of the epoxy primer comprises the following steps:
[0052] S11, polyethylene glycol monomethyl ether 2000, dodecyl succinic anhydride, phthalic anhydride were mixed, heated and stirred at 100°C for 4 hours, epoxy resin E51 and triphenylphosphine were added, heated and stirred at 120°C for 4 hours, and material A was obtained; the mass ratio of polyethylene glycol monomethyl ether 2000, dodecyl succinic anhydride, phthalic anhydride, epoxy resin E51, and triphenylphosphine was 30:3:1:90:0.2;
[0053] S12, take the material A and deionized water, mix them, stir for 7 hours, add dipropylene glycol butyl ether, propylene glycol methyl ether, defoamer GP-330, Digo BYK153 wetting agent, BASF dispersant Tamol NN 9401, mixed etherified glycoluril resin, sodium nitrite, calcium ion exchange silica anti-rust pigment, BYK410 rheological additive, stir for 5 hours, and obtain the epoxy primer; the material A, deionized water, dipropylene glycol butyl ether, propylene glycol methyl ether, defoamer GP-330, Digo BYK153 wetting agent, BASF dispersant Tamol NN 9401, the mass ratio of mixed etherified glycoluril resin, sodium nitrite, calcium ion exchange silica anti-rust pigment and BYK410 rheological additive is 50:30:0.4:0.2:0.4:0.2:0.2:0.6:0.2:0.06:0.2;
[0054] The preparation method of the polyurethane topcoat comprises the following steps:
[0055] S21, taking butyl-decanoic acid ketone, terephthalic acid methanol, and diphenyl phosphate, mixing, stirring for 12 hours, and obtaining material B; the mass ratio of butyl-decanoic acid ketone, terephthalic acid methanol, and diphenyl phosphate is 7:1.2:0.3;
[0056] S22, mixing graphene oxide powder, deionized water, p-phenylenediamine and ammonia water, ultrasonically dispersing at 90° C. for 3 h, filtering, washing the solid phase, and drying to obtain material C; the amount ratio of the graphene oxide powder, deionized water, p-phenylenediamine and ammonia water is 50 mg: 100 mL: 0.4 g: 0.8 mL; the concentration of the ammonia water is 2 mol / L;
[0057] S23, taking the material C, deionized water, and dodecylbenzenesulfonic acid, mixing, ultrasonically dispersing at 50°C for 3h, adding aniline, stirring for 20min, adding ammonium persulfate, stirring in an ice-water bath for 8h, filtering, washing the solid phase, and drying to obtain material D; the mass ratio of the material C, deionized water, dodecylbenzenesulfonic acid, aniline, and ammonium persulfate is 0.4:50:0.04:1.2:0.04;
[0058] S24, taking the material D, hydrophobic fumed silica, anhydrous ethanol, and polydimethylsiloxane, mixing, ultrasonically dispersing for 2 hours, drying at 50° C. for 6 hours, filtering, washing the solid phase, and drying to obtain the surface hydrophobic agent; the mass ratio of the material D, hydrophobic fumed silica, anhydrous ethanol, and polydimethylsiloxane is 2:0.45:80:0.12;
[0059] S25. In a condensing reflux reactor, mix isophorone diisocyanate, 4-methoxyphenol, dibutyltin dilaurate, and ethyl acetate, stir for 30 minutes, add triethylene glycol, stir at 45°C for 30 minutes, heat to 50°C, continue stirring for 3 hours, heat to 65°C, add material B, stir for 3 hours, heat to 80°C, add hydroxyethyl acrylate, stir for 4 hours, filter, take the liquid phase, add acrylate isobornyl, adhere to The adhesion promoter JSC-505 and the surface hydrophobic agent are stirred for 3 hours to obtain the polyurethane topcoat; the mass ratio of isophorone diisocyanate, 4-methoxyphenol, dibutyltin dilaurate, ethyl acetate, triethylene glycol, material B, hydroxyethyl acrylate, isobornyl acrylate, adhesion promoter JSC-505 and the surface hydrophobic agent is 70:1.2:0.08:25:2:2:3:0.8:0.3:1.2.
[0060] Comparative Example 1
[0061] The difference from Example 1 is that the preparation process of step S11 includes the following steps:
[0062] S11. Mix polyethylene glycol monomethyl ether 2000 and dodecyl succinic anhydride, heat and stir at 90°C for 3 h, add epoxy resin E51 and triphenylphosphine, heat and stir at 110°C for 3 h, and obtain material A; the mass ratio of polyethylene glycol monomethyl ether 2000, dodecyl succinic anhydride, epoxy resin E51, and triphenylphosphine is 25:2.8:80:0.1.
[0063] Comparative Example 2
[0064] The difference from Example 1 is that the preparation process of step S11 includes the following steps:
[0065] S11. Mix polyethylene glycol monomethyl ether 2000 and phthalic anhydride, heat and stir at 90°C for 3 h, add epoxy resin E51 and triphenylphosphine, heat and stir at 110°C for 3 h, and obtain material A; the mass ratio of polyethylene glycol monomethyl ether 2000, phthalic anhydride, epoxy resin E51, and triphenylphosphine is 25:2.8:80:0.1.
[0066] Comparative Example 3
[0067] The difference from Example 1 is that material B is not added in the preparation process of the polyurethane topcoat.
[0068] Comparative Example 4
[0069] The difference from Example 1 is that p-phenylenediamine is not added in the preparation process of step S22.
[0070] Comparative Example 5
[0071] The difference from Example 1 is that the preparation method of the polyurethane topcoat comprises the following steps:
[0072] S21, mixing butyl-decanoic acid ketone, terephthalic acid methanol and diphenyl phosphate, stirring for 10 hours to obtain material B; the mass ratio of butyl-decanoic acid ketone, terephthalic acid methanol and diphenyl phosphate is 6:1:0.2;
[0073] S22, mixing graphene oxide powder, deionized water, p-phenylenediamine and ammonia water, ultrasonically dispersing at 80° C. for 2 h, filtering, washing the solid phase, and drying to obtain material C; the amount ratio of the graphene oxide powder, deionized water, p-phenylenediamine and ammonia water is 50 mg: 100 mL: 0.3 g: 0.6 mL; the concentration of the ammonia water is 1 mol / L;
[0074] S23, mixing the material C, deionized water and dodecylbenzenesulfonic acid, dispersing by ultrasonic at 40° C. for 2 h, filtering, washing the solid phase, and drying to obtain material D; the mass ratio of the material C, deionized water and dodecylbenzenesulfonic acid is 0.2:50:0.02;
[0075] S24, taking the material D, hydrophobic fumed silica, anhydrous ethanol, and polydimethylsiloxane, mixing, ultrasonically dispersing for 1 hour, drying at 50° C. for 4 hours, filtering, washing the solid phase, and drying to obtain the surface hydrophobic agent; the mass ratio of the material D, hydrophobic fumed silica, anhydrous ethanol, and polydimethylsiloxane is 1:0.4:70:0.1;
[0076] S25. In a condensing reflux reactor, mix isophorone diisocyanate, 4-methoxyphenol, dibutyltin dilaurate and ethyl acetate, stir for 20 min, add triethylene glycol, stir at 35-45 ° C for 20 min, heat to 50 ° C, continue stirring for 2 h, heat to 55 ° C, add material B, stir for 2 h, heat to 80 ° C, add hydroxyethyl acrylate, stir for 3 h, filter, take the liquid phase, add acrylate isobornyl, Adhesion promoter JSC-505 and surface hydrophobic agent are stirred for 2 hours to obtain the polyurethane topcoat; the mass ratio of isophorone diisocyanate, 4-methoxyphenol, dibutyltin dilaurate, ethyl acetate, triethylene glycol, material B, hydroxyethyl acrylate, isobornyl acrylate, adhesion promoter JSC-505 and surface hydrophobic agent is 60:1:0.06:20:1:1:2:0.6:0.2:0.8.
[0077] Comparative Example 6
[0078] The difference from Example 1 is that the preparation method of the polyurethane topcoat comprises the following steps:
[0079] S21, mixing butyl-decanoic acid ketone, terephthalic acid methanol and diphenyl phosphate, stirring for 10 hours to obtain material B; the mass ratio of butyl-decanoic acid ketone, terephthalic acid methanol and diphenyl phosphate is 6:1:0.2;
[0080] S22, mixing graphene oxide powder, deionized water, p-phenylenediamine and ammonia water, ultrasonically dispersing at 80° C. for 2 h, filtering, washing the solid phase, and drying to obtain material C; the amount ratio of the graphene oxide powder, deionized water, p-phenylenediamine and ammonia water is 50 mg: 100 mL: 0.3 g: 0.6 mL; the concentration of the ammonia water is 1 mol / L;
[0081] S23, take the material C, deionized water, dodecylbenzenesulfonic acid, mix, ultrasonically disperse at 40 ° C for 2h, add aniline, stir for 10min, add ammonium persulfate, stir in an ice water bath for 6h, filter, wash the solid phase, dry, and obtain material D, that is, the surface hydrophobic agent; the mass ratio of the material C, deionized water, dodecylbenzenesulfonic acid, aniline, and ammonium persulfate is 0.2:50:0.02:1:0.02;
[0082] S24. In a condensing reflux reactor, mix isophorone diisocyanate, 4-methoxyphenol, dibutyltin dilaurate and ethyl acetate, stir for 20 min, add triethylene glycol, stir at 35-45 ° C for 20 min, heat to 50 ° C, continue stirring for 2 h, heat to 55 ° C, add material B, stir for 2 h, heat to 80 ° C, add hydroxyethyl acrylate, stir for 3 h, filter, take the liquid phase, add acrylate isobornyl, Adhesion promoter JSC-505 and surface hydrophobic agent are stirred for 2 hours to obtain the polyurethane topcoat; the mass ratio of isophorone diisocyanate, 4-methoxyphenol, dibutyltin dilaurate, ethyl acetate, triethylene glycol, material B, hydroxyethyl acrylate, isobornyl acrylate, adhesion promoter JSC-505 and surface hydrophobic agent is 60:1:0.06:20:1:1:2:0.6:0.2:0.8.
[0083] Performance Testing
[0084] Water vapor transmission rate test is carried out according to standard GB / T 1037-2021;
[0085] Water absorption test is carried out according to standard GB / T 1034-2008;
[0086] Adhesion test according to standard ISO 2409-2007;
[0087] The water contact angle was tested by the hanging drop method using a KrassDSA100 surface contact angle meter at a temperature of 25°C. Five different locations of the same sample were selected for measurement, and the average value was taken as the final result of the contact angle.
[0088] The two-component waterborne polyurethane adhesives prepared in Examples 1-3 and Comparative Examples 1-6 were respectively coated on the surface of 70×70×20 mm cement mortar specimen substrates, and baked at 105° C. for 10 min. After curing, the coating thickness was 5 μm. Performance tests were carried out according to the above standards. The test results are shown in Table 1 below.
[0089] Table 1
[0090]
[0091]
[0092] As can be seen from Table 1, the two-component waterborne polyurethanes prepared in Examples 1-3 of the present application have excellent water resistance and hydrophobic properties.
[0093] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a two-component waterborne polyurethane adhesive, characterized in that: The following steps are involved: The epoxy primer and the polyurethane topcoat are mixed evenly in a volume ratio of 1-1.2:1.5-2.5 to obtain the two-component waterborne polyurethane adhesive; The preparation method of the epoxy primer comprises the following steps: S11, mix polyethylene glycol monomethyl ether 2000, dodecyl succinic anhydride and phthalic anhydride, heat and stir at 90-100° C. for 3-4 hours, add epoxy resin E51 and triphenylphosphine, heat and stir at 110-120° C. for 3-4 hours to obtain material A; S12, taking the material A and deionized water, mixing, stirring for 5-7h, adding dipropylene glycol butyl ether, propylene glycol methyl ether, defoamer GP-330, Digo BYK153 wetting agent, BASF dispersant Tamol NN 9401, mixed etherified glycoluril resin, sodium nitrite, calcium ion exchange silica anti-rust pigment, BYK410 rheological additive, stirring for 4-5h, and obtaining the epoxy primer; The preparation method of the polyurethane topcoat comprises the following steps: S21, mixing butyl-decanoic acid, terephthalic acid methanol and diphenyl phosphate, and stirring for 10-12 hours to obtain material B; S22, mixing graphene oxide powder, deionized water, p-phenylenediamine and ammonia water, dispersing by ultrasonic at 80-90° C. for 2-3 h, filtering, washing and drying the solid phase to obtain material C; S23, taking the material C, deionized water, and dodecylbenzenesulfonic acid, mixing them, ultrasonically dispersing them at 40-50° C. for 2-3 hours, adding aniline, stirring for 10-20 minutes, adding ammonium persulfate, stirring in an ice-water bath for 6-8 hours, filtering, washing the solid phase, and drying to obtain material D; S24, taking the material D, hydrophobic fumed silica, anhydrous ethanol, and polydimethylsiloxane, mixing, ultrasonically dispersing for 1-2 hours, drying at 50° C. for 4-6 hours, filtering, washing, and drying the solid phase to obtain a surface hydrophobic agent; S25. In a condensing reflux reactor, take isophorone diisocyanate, 4-methoxyphenol, dibutyltin dilaurate, and ethyl acetate, mix, stir for 20-30 minutes, add triethylene glycol, stir at 35-45°C for 20-30 minutes, heat to 50°C, continue stirring for 2-3 hours, heat to 55-65°C, add material B, stir for 2-3 hours, heat to 80°C, add hydroxyethyl acrylate, stir for 3-4 hours, filter, take the liquid phase, add isobornyl acrylate, adhesion promoter JSC-505, and surface hydrophobic agent, stir for 2-3 hours, and obtain the polyurethane topcoat.
2. The method for preparing a two-component waterborne polyurethane adhesive according to claim 1, characterized in that: In step S11, the mass ratio of polyethylene glycol monomethyl ether 2000, dodecyl succinic anhydride, phthalic anhydride, epoxy resin E51, and triphenylphosphine is 25-30:2-3:0.8-1:80-90:0.1-0.
2.
3. The method for preparing a two-component waterborne polyurethane adhesive according to claim 1, characterized in that: In step S12, the mass ratio of material A, deionized water, dipropylene glycol butyl ether, propylene glycol methyl ether, defoamer GP-330, Digo BYK153 wetting agent, BASF dispersant Tamol NN 9401, mixed etherified glycoluril resin, sodium nitrite, calcium ion exchange silica anti-rust pigment, and BYK410 rheological additive is 40-50:20-30:0.2-0.4:0.1-0.2:0.2-0.4:0.1-0.2:0.1-0.2:0.5-0.6:0.1-0.2:0.05-0.06:0.1-0.
2.
4. The method for preparing a two-component waterborne polyurethane adhesive according to claim 1, characterized in that: In step S21, the mass ratio of butyl-decanolide, 4-dimethylol and diphenyl phosphate is 6-7: 1-1.2: 0.2-0.
3.
5. The method for preparing a two-component waterborne polyurethane adhesive according to claim 1, characterized in that: In step S22, the dosage ratio of the graphene oxide powder, deionized water, p-phenylenediamine, and ammonia water is 50 mg: 100 mL: 0.3-0.4 g: 0.6-0.8 mL; the concentration of the ammonia water is 1-2 mol / L.
6. The method for preparing a two-component waterborne polyurethane adhesive according to claim 1, characterized in that: In step S23, the mass ratio of the material C, deionized water, dodecylbenzenesulfonic acid, aniline and ammonium persulfate is 0.2-0.4:50:0.02-0.04:1-1.2:0.02-0.
04.
7. The method for preparing a two-component waterborne polyurethane adhesive according to claim 1, characterized in that: In step S24, the mass ratio of the material D, hydrophobic fumed silica, anhydrous ethanol and polydimethylsiloxane is 1-2: 0.4-0.45: 70-80: 0.1-0.
12.
8. The method for preparing a two-component waterborne polyurethane adhesive according to claim 1, characterized in that: In step S25, the mass ratio of isophorone diisocyanate, 4-methoxyphenol, dibutyltin dilaurate, ethyl acetate, triethylene glycol, material B, hydroxyethyl acrylate, isobornyl acrylate, adhesion promoter JSC-505, and surface hydrophobic agent is 60-70: 1-1.2: 0.06-0.08: 20-25: 1-2: 1-2: 2-3: 0.6-0.8: 0.2-0.3: 0.8-1.
2.
9. A two-component waterborne polyurethane adhesive prepared by the preparation method according to any one of claims 1 to 8.
10. The use of the two-component waterborne polyurethane adhesive according to claim 9, characterized in that: The application is for building waterproofing.
Citation Information
Patent Citations
Water-based anticorrosive coating for transformer and preparation method of water-based anticorrosive coating
CN110591507A
Waterborne epoxy wet-on-wet polyurethane matched paint applied to engineering machinery and preparation method of waterborne epoxy wet-on-wet polyurethane matched paint
CN112876962A
Automotive water-based paint and preparation method thereof
CN116063898A
Waterborne epoxy / polyurethane composite coating for engineering machinery and preparation method of waterborne epoxy / polyurethane composite coating
CN118291008A
Urethane-based paint film waterproofing method
JP2002364128A
